2020
DOI: 10.1029/2019jd032283
|View full text |Cite
|
Sign up to set email alerts
|

Erythemal Radiation, Column Ozone, and the North American Monsoon

Abstract: Recently, Anderson et al. (2012, https://doi.org/10.1126/science.1222978, 2017, https://doi.org/10.1073/pnas.1619318114) and Anderson and Clapp (2018, https://doi.org/10.1039/C7CP08331A) proposed that summertime convectively injected water vapor over North America could lead to stratospheric ozone depletion through halogenic catalytic reactions. Such ozone loss would reduce the ozone column and increase erythemal daily dose (EDD). Using 10 years of observations over the North American monsoon region from the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…However, a potential ozone destruction in the midlatitude lowermost stratosphere due to heterogeneous chlorine activation was discussed in previous studies (e.g. Keim et al, 1996;Anderson et al, 2012Anderson et al, , 2017Anderson and Clapp, 2018;Schwartz et al, 2013;Berthet et al, 2017;Robrecht et al, 2019;Clapp and Anderson, 2019;Schoeberl et al, 2020). This chlorine-driven ozone loss process could occur today above central North America in relation to stratospheric moistening through convective overshooting events during the North American Summer Monsoon (NAM).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, a potential ozone destruction in the midlatitude lowermost stratosphere due to heterogeneous chlorine activation was discussed in previous studies (e.g. Keim et al, 1996;Anderson et al, 2012Anderson et al, , 2017Anderson and Clapp, 2018;Schwartz et al, 2013;Berthet et al, 2017;Robrecht et al, 2019;Clapp and Anderson, 2019;Schoeberl et al, 2020). This chlorine-driven ozone loss process could occur today above central North America in relation to stratospheric moistening through convective overshooting events during the North American Summer Monsoon (NAM).…”
Section: Discussionmentioning
confidence: 90%
“…In comparison, Schwartz et al (2013) argue that conditions cold and moist enough for chlorine activation are very rare and are usually associated with low HCl and ozone amounts. Schoeberl et al (2020) found that lowermoststratospheric H 2 O is increased during the NAM caused by enhanced convection followed by advection in the monsoon circulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the algorithm uses precipitation data together with infrared brightness temperature from geostationary satellites to determine the heights of convective clouds. This near-global cloud top product has been used to diagnose convective influence in a large number of trajectory studies (e.g., Bergman et al, 2012;Pfister et al, 2001;Schoeberl et al, 2019Schoeberl et al, , 2020Ueyama et al, 2014Ueyama et al, , 2018. Cloud top height data are made available every 3 h on a 0.25° longitude × 0.25° latitude grid in the 60°S-60°N domain.…”
Section: Satellite-based Convective Cloud Productmentioning
confidence: 99%